Kajian perhubungan antara identiti diri dengan norma subjektif terhadap tingkah laku sisa sifar dalam kalangan pengguna di Lembah Klang - Mustafa, Fazlina Akmal; Muhammad Arif, Afida Mastura; Abu Bakar, Elistina (Malaysian Consumer and Family Economics Association, 2016)
Solid waste management has become one of Malaysia’s critical environmental issues. The increase of generation of waste and the high cost in its management is a challenge to the authorities. The study is aimed at determining the level of self-identity and subjective norm towards zero waste behaviour among consumers in Klang Valley. A total of 400 respondents were selected through multi-stage random sampling in this study. The survey was conducted using self-administered questionnaire to obtain information on the respondents’ socio-demographic background, self-identity, subjective norms and zero waste behaviour. Research findings show that respondents’ level of self-identity, subjective norms and zero waste behaviour were moderate. The results show that zero waste behaviour significantly correlates with self-identity (r=0.490*, p<0.01) and subjective norm (r=0.463*, p<0.01). The variables used in this study contributed 29.7% towards the model. Multiple regression result found that self-identity is the most significant factor to influence consumer behaviour towards zero waste. Therefore, appropriate effective strategies to build a strong self-identity towards environment should be developed by the relevant authorities to enhance zero waste behaviour among the consumers.